Selektivno letenje i njegove odrednice kao prvi stupanj odabira kandidata za pilotski poziv - Njari, Josip (Promet - Traffic&Transportation, 2012)
Flying as the vocational commitment of a person makes one of the most complex aspects of human activity. The beginning of materialization of such professional orientation refers to the selection of candidates for student-pilots at the Faculty of Traffic Engineering, Department of Aeronautical Engineering (Croatian Air Force Pilots). To become a student of aeronautical engineering at the Faculty of Traffic Engineering means having successfully passed a series of medical, psychiatric, psychological, and admissions examinations for this particular line of university course of studies for a degree. The import of selection of candidates in the process of selective flight training of student-pilots rests in the highly professional approach to the first level of training of student· -pilots resulting in the maximum economy of costs and confident and undoubted assessment of the capacities of a student- pilot in future execution of assignments in units of the Croatian Air Force. The Zagreb University Faculty of Traffic Engineering, Croatian Air Force and Antiaircraft Defense cooperate in the education and training of students for a degree in aeronautical engineering.